The complexities of managing historic buildings with BIM. Issue 2 (15th May 2020) - Charlton, James; Kelly, Kenneth; Greenwood, David; Moreton, Leo
Abstract : Purpose: The adoption of building information modelling (BIM) in managing built heritage is an exciting prospect, but one that presents complexities additional to those of modern buildings. If challenges can be identified and overcome, the adoption of historic BIM (HBIM) could offer efficiencies in how heritage buildings are managed. Design/methodology/approach: Using Durham Cathedral as a case study, we present the workflows applied to create an asset information model to improve the way this unique UNESCO World Heritage Site is managed, and in doing so, set out the challenges and complexities in achieving an HBIM solution. Findings: This study identifies the need for a better understanding of the distinct needs and context for managing historic assets, and the need for heritage information requirements (HIR) that reflect this. Originality/value: This study presents first-hand findings based on a unique application of BIM at Durham Cathedral, a UNESCO World Heritage Site. The study provides a better understanding of the challenges and drivers of HBIM adoption across the heritage sector and underlines the need for information requirements that are unique to historical buildings/assets to deliver a coherent and relevant HBIM approach.